Peran Guru Penggerak Untuk Mewujudkan Karakter Siswa menggunakan Profil Pelajar Pancasila pada Abad 21 - Muzakky, Mohamad Irvan (Proceedings Series of Educational Studies, 2024)
Abstract This study aims to 1) Know how important the role of mobilizing teachers through the Pancasila student profile in children's character education; 2) Know what indicators are contained in the driving teacher in character education; 3) Know what indicators are contained in the Pancasila student profile in character education. This research uses library research. The results of this study are: 1) Teacher competence is very important in implementing the profile of Pancasila students in character education; 2) Teacher indicators driving character education, namely by driving change and example; 3) Pancasila student profile indicator, namely by cultivating the soul 1) Faith; 2) Global Diversity; 3) Mutual Cooperation; 4) Independence; and 5) Fear of God Almighty and Noble Character. 5) Analytical thinking; 6) Original. Abstrak Penelitian ini bertujuan untuk 1) Mengetahui bagaimana pentingnya peran guru penggerak melalui profil pelajar pancasila dalam pendidikan karakter anak; 2) Mengatahui indicator apa saja yang terdapat dalam guru penggerak dalam pendidikan karakter; 3) Mengetahui indicator apa saja yang terdapat dalam profil pelajar Pancasila dalam pendidikan karakter. Penelitian ini menggunakan studi pustaka (library research). Hasil dari penelitian ini yaitu: 1) Kompetensi guru sangat penting dalam mengimplimentasikan profil pelajar pancasila dalam pendidikan karakter; 2) Indikator guru penggerak untuk pendidikan karakter yaitu dengan penggerak perubahan dan tauladan; 3) indokator profil pelajar Pancasila yaitu dengan menumbuhkan jiwa 1) Beriman, Bertakwa, dan Berakhlak Mulia; 2) Berkebinekaan Global; 3) Bergotong royong; 4) Mandiri; 5) Berpikir Kritis; 6) Kreatif.